2020
DOI: 10.1017/s1368980020000464
|View full text |Cite
|
Sign up to set email alerts
|

Household food insecurity: associations with disordered eating behaviours and overweight in a population-based sample of adolescents

Abstract: Objective: To examine how household food insecurity is related to adolescent weight status and disordered eating. Design: Cross-sectional, population-based study. Adolescents self-reported unhealthy weight control behaviours, binge eating and meal frequency; weight status was measured. Household food insecurity was assessed by asking parents to respond to the validated six-item US Household Food Security Survey Module. Setting: Adolescents surveyed within Minneapolis/St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 69 publications
3
35
1
1
Order By: Relevance
“…These findings provide further support for an established need to develop interventions to reach emerging adults experiencing financial difficulties (Becker, Middlemass, Gomez, & Martinez‐Abrego, 2019; Tester, Lang, & Laraia, 2016). Moreover, the present finding is consistent with findings from EAT 2010, wherein adolescents experiencing food insecurity reported a higher rate of UWCBs relative to those who did not experience food insecurity (Hooper, Telke, Larson, Mason, & Neumark‐Sztainer, 2020). While the present study did not support an association between food insecurity and binge eating, previous research with the EAT 2010–2018 cohort suggests that food insecurity may be positively associated with binge eating (Larson, Laska, & Neumark‐Sztainer, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…These findings provide further support for an established need to develop interventions to reach emerging adults experiencing financial difficulties (Becker, Middlemass, Gomez, & Martinez‐Abrego, 2019; Tester, Lang, & Laraia, 2016). Moreover, the present finding is consistent with findings from EAT 2010, wherein adolescents experiencing food insecurity reported a higher rate of UWCBs relative to those who did not experience food insecurity (Hooper, Telke, Larson, Mason, & Neumark‐Sztainer, 2020). While the present study did not support an association between food insecurity and binge eating, previous research with the EAT 2010–2018 cohort suggests that food insecurity may be positively associated with binge eating (Larson, Laska, & Neumark‐Sztainer, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Since this review, new analyses have been added to the mixed literature base. In a recent study, though there was a higher prevalence of overweight in food-insecure children, this was no longer significant after adjustment for other demographic factors [37]. Adding to the literature base suggesting a positive association, one study at a weight management clinic found that children from food-insecure households (N = 822) had higher BMI percentiles than those from food-secure households [59], and an analysis from the 2011 Kindergarten Cohort 2011 of the Early Childhood Longitudinal Study (ECLS) showed that first-grade food insecurity is an independent risk factor for longitudinal increases in BMI z-score in first through third grades [60].…”
Section: Food Insecurity and Obesity In Childrenmentioning
confidence: 85%
“…While participants in all groups had anecdotes about overeating in their children, only respondents in the food-insecure groups described food-hiding, night-time eating episodes, and binge-type eating behaviors [36]. In an analysis of middle and high school adolescents who participated in two studies in Minnesota-EAT 2010 (Eating and Activity in Teens) and Project F-EAT (Families and Eating and Activity Among Teens)-the prevalence of unhealthy weight control behaviors was higher among adolescents who were food-insecure (44.5%) compared to food-secure peers (37.8%, p < 0.001), after adjusting for parental education, race/ethnicity, sex, and age [37]. In related analysis of adolescents in Project EAT over time, food insecurity in early/ middle adolescence (EAT-I) predicted increased risk of binge eating 5 years later during late adolescence/early adulthood (EAT-II) [38].…”
Section: Food Insecurity Chronic Stress and Eating Behaviorsmentioning
confidence: 97%
“…While eating disorders were historically believed to occur most commonly in affluent populations, eating disorders are now recognized to affect individuals across all socioeconomic strata [ 22 ]. Moreover, in recent years, individuals living in food-insecure households have demonstrated higher levels of overall eating disorder pathology [ 14 , 15 ], more eating disorder symptoms such as binge eating [ 14 , 15 , 23 , 24 ] and compensatory behaviors (e.g., self-induced vomiting, laxative use) [ 14 , 15 , 25 ], and greater likelihood of meeting diagnostic criteria for bulimia nervosa [ 17 ] and binge-eating disorder [ 16 ] as assessed via self-administered questionnaire. However, no studies to date have examined the association between food insecurity and eating disorders using eating disorder data gleaned via diagnostic interview, which offers important advantages over self-administered questionnaire data (e.g., the opportunity for interviewers to probe for thoughtful responses [ 26 ]), and most prior studies have utilized convenience samples.…”
Section: Introductionmentioning
confidence: 99%